Analysis of anatomy and configuration of the canal system of the maxillary second premolar in the population of Bosnia and Herzegovina - Brankica Davidović; Ljiljana Bjelović; Igor Radović; Bojana Davidović; Svjetlana Janković; Smiljka Cicmil (Биомедицинска истраживања, 2021)
Introduction: Successful endodontic treatment depends upon the clinician's knowledge and ability to recognize and diagnose the presence of anatomical and morphological variations of the root and canal system. The aim of this study was to establish the number of roots and root canal configurations of the maxillary second premolar in the population of Bosnia and Herzegovina. Methods: The study sample was comprised of 150 maxillary second premolar teeth extracted for orthodontic or prosthetic reasons. Endodontic drills were used for trepanation of cavum dentis, and the number and patency of each root canal were determined by Kexpander # 15. Then, the samples were decalcified, made transparent and colored, to enable 3D viewing of the canal system. Decalcified teeth were observed from two projections (clinical and approximal) and analyzed in detail with a magnifying glass under 3 × and 5 × magnification in order to determine the number of roots, number of canals, root canal configuration using Vertucci's classification and number of anastomoses between canals. Statistical significance was obtained using Chi-square test. Results: The results obtained by decalcification of the teeth showed that, by radiographic analysis from the clinical projection, all the teeth had a single root. While, by the analysis from the approximal projection, 94.0% had one, 6.0% two roots. From the approximal projection, 70.7% with a single root canal and 29.3% with two root canals are visualized. The most common type of root canal configuration in the maxillary second premolars was Type I in both clinical (87.9%) and approximal projection (40.7%). Conclusion: These results emphasize the importance of knowing the variations in root canal morphology, because excluding the possibility of morphological variations can lead to failure of endodontic therapy
Keywords: maxillary second premolar; root canal; decalcification